Analysis of the Application of Storytelling and Flashcards - Riyadi, Agung Afif; Sari, Sintia; Hasanah, Hizrotun; Nurjaman, Iman (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
The need for English language learning for early childhood is very high, especially in the context of developing students' skills at the PAUD level. The progress of a nation requires its people to be proficient in using English. Therefore, the Indonesian education system is currently trying to introduce English as an international language to early childhood students. English language education is highly recommended if introduced to young children. Especially before the age of 12 years. The early childhood category includes those aged 2 to 7 years. This age stage is a golden moment for the development of children's language skills. They can understand various languages like native speakers, so this opportunity needs to be utilized to the maximum. Therefore, learning English requires an effective and appropriate teaching process and methods. There are several methods used to teach English, including context which includes game media, experience using cards, namely the flashcard method and storytelling methods using songs and story methods. Storytelling and flashcard methods are suitable and successful methods in the English language learning process for early childhood.